Clinical features of facial mixed skin tumor: a report of 18 cases and literature review - Linghua LIU; Fei XIONG; Liangliang WANG; Pingping WU; Qiuhe SONG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To investigate the clinicopathological features, diagnosis and differential diagnosis of mixed skin tumor. Methods We retrospectively analyzed the data of 18 patients with mixed skin tumors from our department from March 2017 to September 2021. Results The male to female ratio of the 18 cases was 1 ∶1, with the onset age of 24 to 64 years. All patients had facial involvement (most common on the nose), and exhibited asymptomatic singular nodule in light red or skin color. The histological findings revealed mixed skin tumor, including differentiation toward eccrine glands in 3 cases and apocrine glands in 15 cases. None of the 18 patients was clinically diagnosed as mixed skin tumor. All 18 patients underwent surgical resection and were followed up for 2 months to 1 year without recurrence. Conclusions Mixed skin tumor is a rare benign tumor. The diagnosis of the disease is mainly dependent on histopathological examination.